طرق تدريس المفردات في كتاب الـمستوى الأول للـمبتدئين في مركز الدراسات الأساسية، بالجامعة الإسلامية العالمية بماليزيا - Idris, Nor Ashikin; Md Azmi, Afiqah; Arshad, Mastura; Mustapai, Mohd Zulhisyam; Ab Jabbar, Muhammad Bahari; Md Zain, Zairul (2022)
Abstract: The main objective of this research is to investigate the most appropriate methods in teaching vocabulary in the level one textbook for beginners and ways to learn it among the beginner students. In addition, this research aims to find out the teachers' opinions whether the vocabulary in the new textbook matches the students' level. To achieve these goals, the researchers use the analytical descriptive studies by distributing questionnaires related to teaching and learning vocabulary through a Google form. 22 teachers answered this questionnaire, and they are the ones who teach the level one in the Quranic Language Department in the Centre for Foundation Studies of this university, and 140 students also participated in answering the questionnaire, and they have taken the Quranic language level one during the first semester 2022. The result indicates that the most appropriate methods refer to the teacher himself in explaining vocabulary to his beginner students according to their educational background, through presenting pictures or referring to tangible things, using modern platforms and teaching synonyms and antonyms as well as encouraging students to search for the vocabulary meanings in the dictionary, in addition to preparing various exercises in order to motivate students to memorize vocabulary, remember it and use it in correct sentences. From the students’ perspectives, they rely a lot on reading Arabic texts in the textbook as a main source for learning vocabulary, and they prefer to search for meanings from the Internet. The researchers found that the vocabulary chosen by textbook authors is suitable with the beginners’ level, although the textbook is still in dire need of revision because it is one of the first Arabic language teaching books written according to the CEFR curriculum.